Analisis Potensi Pasar Pada Produk Kosmetik Wardah - Imoni Misadiwana; Mentari Salsabila; Syamsul Hidayat (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to analyze the market potential for Wardah cosmetic products. This research method uses qualitative, sampling techniques using random sampling techniques with the process of disseminating statements carried out online and publicly as many as 88 student respondents from Bina Bangsa University who filled out statements. Based on the research results, it shows that the market potential of Wardah cosmetic products is growing rapidly because Wardah products have product quality that is halal certified and Wardah products pamper consumers with the expansion of outlets in malls, supermarkets and traditional markets so that consumers are more likely to decide to purchase Wardah products. even though many similar new products have emerged.